Exploring Soil Factors Determining Composition and Structure of the Bacterial Communities in Saline-Alkali Soils of Songnen Plain - Wang, Shuang; Sun, Lei; Ling, Ning; Zhu, Chen; Chi, Fengqin; Li, Weiqun; Hao, Xiaoyu; Zhang, Wu; Bian, Jingyang; Chen, Lei; Wei, Dan (Frontiers in Microbiology, 2020)
Songnen Plain is originally one of the three major glasslands in China and has now become one of the three most concentrated distribution areas of sodic-saline soil worldwide. The soil is continuously degraded by natural and anthropogenic processes, which has a negative impact on agricultural production. The investigation of microbial diversity in this degraded ecosystem is fundamental for comprehending biological and ecological processes and harnessing the potential of microbial resources. The Illumina MiSeq sequencing method was practiced to investigate the bacterial diversity and composition in saline-alkali soil. The results from this study show that the change in pH under alkaline conditions was not the major contributor in shaping bacterial community in Songnen Plian. The electrical conductivity (EC) content of soil was the most important driving force for bacterial composition (20.83%), and the second most influencing factor was Na+ content (14.17%). Bacterial communities were clearly separated in accordance with the EC. The dominant bacterial groups were Planctomycetes, Proteobacteria and Bacteroidetes among the different salinity soil. As the salt concentration increased, the indicators changed from Planctomycetes and Bacteroidetes to Proteobacteria and Firmicutes. Our results suggest that Proteobacteria and Firmicutes were the main indicator species reflecting changes of the main microbial groups and the EC as a key factor drive the composition of the bacterial community under alkaline conditions in saline-alkali soils of Songnen Plain.